Antioxidant, Physiochemical, and Sensory Properties of Functional Marshmallow Produced from Honey, Strawberry Concentrates, and Hibiscus Extract - Maher M. Al-Dabbas; Etaf G. Abu Samaan; Sehar Iqbal; Hani J. Hamad; Rawan Al-Jaloudi; Mohammad Shahein; Bha’a Aldin Al-Nawasrah; Abdalrahman Al-Zabt; Doa`a Al-Refaie; Nisreen Shehadeh; Mahmoud Abughoush (Foods)
Marshmallow candy is a well-known sugar-based confection that is widely consumed among different population groups. However, its high sugar contents and low nutritive value might lead to adverse health outcomes. This study, therefore, aimed to develop optimal formulations for functional marshmallow candy using honey, aqueous hibiscus extract, cow’s milk, and strawberry concentrates with partial replacement of table sugar and glucose syrup. In this regard, six different formulations (F1–F6) were developed, varying in the ratios of key ingredients, such as F1 formulated with honey (9%), sucrose (35%), glucose syrup (33%), milk (4%), and hibiscus extract (1%); F2 containing honey (10%), sucrose (30%), glucose syrup (25%), milk (4%), hibiscus extract (1%), and strawberry concentrate (13%); F3 with honey (15%), sucrose (25%), glucose syrup (20%), milk (4%), hibiscus extract (1%), and strawberry concentrate (16%); F4 formulated with honey (20%), sucrose (20%), glucose syrup (15%), milk (4%), hibiscus extract (1%), and strawberry concentrate (24%); F5 containing honey (30%), sucrose (20%), glucose syrup (5%), milk (4%), hibiscus extract (1%), and strawberry concentrate (24%); and F6 developed with honey (10%), sucrose (30%), glucose syrup (25%), and strawberry concentrate (16%) without milk or Hibiscus extract. These formulations were evaluated for total phenolic content, total flavonoid content, DPPH radical scavenging activity, and textural and sensory characteristics. The results show that all formulations containing functional ingredients had significantly higher total phenolic and flavonoid contents, along with stronger antioxidant activities in a dose-dependent manner compared to the control. Among the formulations, F5 exhibited the highest phenolic and flavonoids contents (89.8 mg GAE/100 g and 1.62 mg RE/100 g, respectively) and reducing power activity (197.8% equivalent to 30 µg vitamin C). Additionally, F3 and F4 showed the strongest DPPH scavenging activity, with IC50 values of 8.0 and 5.1 mg/mL, respectively. In terms of texture, the hardness of all formulations was comparable to the control, except for F1 and F6. The results for sensory analysis show that all modified marshmallows received higher consumer acceptance in overall liking, appearance, softness, elasticity, lightness, and flavor compared to the control. Overall, this study shows that the use of functional ingredients significantly enhanced the total phenolic and flavonoid content and improved antioxidant activities in marshmallow production. This functional candy can provide nutrient-rich health-promoting ingredients for consumers.